Preclinical modeling of low energy X-rays radiological burn: Dosimetry study by monte carlo simulations and EPR spectroscopy - Guillou, Manon; L’Homme, Bruno; Trompier, François; Gruel, Gaëtan; Prezado, Yolanda; Dos Santos, Morgane (Frontiers in Physiology, 2022)
Interventional radiology has grown considerably over the last decades and become an essential tool for treatment or diagnosis. This technique is mostly beneficial and mastered but accidental overexposure can occur and lead to the appearance of deterministic effects. The lack of knowledge about the radiobiological consequences for the low-energy X-rays used for these practices makes the prognosis very uncertain for the different tissues. In order to improve the radiation protection of patients and better predict the risk of complications, we implemented a new preclinical mouse model to mimic radiological burn in interventional radiology and performed a complete characterization of the dose deposition. A new setup and collimator were designed to irradiate the hind legs of 15 mice at 30 Gy in air kerma at 80 kV. After irradiation, mice tibias were collected to evaluate bone dose by Electron Paramagnetic Resonance (EPR) spectroscopy measurements. Monte Carlo simulations with Geant4 were performed in simplified and voxelized phantoms to characterize the dose deposition in different tissues and evaluate the characteristics of secondary electrons (energy, path, momentum). 30 mice tibias were collected for EPR analysis. An average absorbed dose of 194.0 ± 27.0 Gy was measured in bone initially irradiated at 30 Gy in air kerma. A bone to air conversion factor of 6.5 ± 0.9 was determined. Inter sample and inter mice variability has been estimated to 13.9%. Monte Carlo simulations shown the heterogeneity of the dose deposition for these low X-rays energies and the dose enhancement in dense tissue. The specificities of the secondary electrons were studied and showed the influence of the tissue density on energies and paths. A good agreement between the experimental and calculated bone to air conversion factor was obtained. A new preclinical model allowing to perform radiological burn in interventional radiology-like conditions was implemented. For the development of new preclinical radiobiological model where the exact knowledge of the dose deposited in the different tissues is essential, the complementarity of Monte Carlo simulations and experimental measurements for the dosimetric characterization has proven to be a considerable asset.